An application of GIS analysis on structural data from metamorphic rocks in Santorini Island. - Marsellos Α. Ε.; Foster, D. A.; Min, K.; Kidd, W. S.F.; Garver, J.; Kyriakopoulos, K. (Bulletin of the Geological Society of Greece, 2013)
The Santorini volcanic island is located in the northern Cretan Sea and is part of the ecent subduction-related volcanic arc. The opening of Cretan Sea is the result of extension associated with a series of ductile and brittle detachment faults developed since the Middle Miocene. A detachment between two exhumed metamorphic units is exposed at Athinios, on Santorini Island. Two exhumed metamorphic units are identified that show evidence of similar brittle deformation, but distinctive ductile and ductile-brittle structures. Different thermal histories indicate that a Miocene metamorphic unit is juxtaposed structurally below an Eocene metamorphic unit. In this paper, a prediction map of structural observations in Athinios is generated with statistical and GIS software, and shows a spatial distribution consistent with the exposure of two metamorphic units. K-Mean Cluster analysis using SPSS software on lineation azimuths of the metamorphic rock units shows two populations with center values of 347.2o ± 0.73o degrees (NNW to N) and 003.4o ± 0.83o degrees (N to NNE). NNW-lineation (arc-parallel extension) population belongs to the lower Miocene metamorphic unit and the NNE-lineation represents the Eocene metamorphic unit that was affected by arc-normal extension. A geostatistical map of ordinary Kriging type displays the possible exposed tectonic contacts. This methodology provides a structural prediction map that after field verification facilitates efficient structural and thermochronological sampling.